2017
DOI: 10.1186/s12875-017-0608-2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to use of non-pharmacological treatments in chronic pain

Abstract: BackgroundConsensus guidelines recommend multi-modal chronic pain treatment with increased uptake of non-pharmacological pain treatment modalities (NPMs). We aimed to identify the barriers and facilitators to uptake of evidence-based NPMs from the perspectives of patients, nurses and primary care providers (PCPs).MethodsWe convened eight separate groups and engaged each in a Nominal Group Technique (NGT) in which participants: (1) created an individual list of barriers (and, in a subsequent round, facilitators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
179
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(189 citation statements)
references
References 39 publications
8
179
0
2
Order By: Relevance
“…Our review also demonstrates that certain non-pharmacological interventions, which were suggested to be less prone to the occurrence of undesirable side effects [53], can be effective in symptom management and enhancing QOL. For example, psychotherapeutic interventions such as yoga could effectively reduce fatigue among breast cancer survivors, while cognitive behavioral therapy could help address sleep disturbance, enhance survivors' QOL, and reduce their perceived burden of hot flashes and night sweats.…”
Section: Discussionmentioning
confidence: 75%
“…Our review also demonstrates that certain non-pharmacological interventions, which were suggested to be less prone to the occurrence of undesirable side effects [53], can be effective in symptom management and enhancing QOL. For example, psychotherapeutic interventions such as yoga could effectively reduce fatigue among breast cancer survivors, while cognitive behavioral therapy could help address sleep disturbance, enhance survivors' QOL, and reduce their perceived burden of hot flashes and night sweats.…”
Section: Discussionmentioning
confidence: 75%
“…Several barriers to implementation of non-pharmacological methods had also been identi ed such as knowledge and experience of the nurse, availability of time, heavy workload, patients' uncooperativeness and local policies and procedures (15,17). In actual situation nurses experience a lot of hurdles to execute and use the non-pharmacological methods, which are in uenced by various factors, such as prolonged course of treatment, time required, and perceived pain or stress that may accompany engagement in nonpharmacological methods were identi ed as a barriers by the nurses (18). Among many others, lack of administrative support, lack of resources, nurses' heavy work load, shortage of nurses, lack of nurse's knowledge and lack of patient's cooperation were some of the few mentioned barriers towards the practice of non-pharmacological methods (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is lack of empirical evidence guiding multiple aspects of opioid prescribing practices for cancer patients (Paice et al, 2016) and a number of inconsistencies among existing national pain management guidelines (Meghani & Vapiwala, 2018), underscoring a need to further expand knowledge on opioid management for cancer pain. Careful pharmacological management of cancer pain continues to be important for optimal pain control and function, especially until there is consistent access to nonopioid and nonpharmacological treatments for chronic pain, which remains limited in the United States (Becker et al, 2017;Meghani & Vapiwala, 2018).…”
Section: Discussionmentioning
confidence: 99%